Photonuclear reactions of calcium isotopes calculated with the nuclear shell model. (July 2015) - Utsuno, Yutaka; Shimizu, Noritaka; Otsuka, Takaharu; Ebata, Shuichiro; Honma, Michio
Abstract: Photoabsorption cross sections in calcium isotopes are investigated theoretically with the most advanced nuclear-structure calculations using the nuclear shell model. We show that the photoabsorption cross sections in 48 Ca dominated by a giant dipole resonance (GDR) are well reproduced with the shell model and predict that a pygmy dipole resonance (PDR) appears in 52 Ca in the low-energy tail of GDR. Excellent agreement with the experiment is achieved due to highly correlated many-body wave functions obtained by treating a huge matrix with the dimension of ∼10 10 . Highlights: We calculate photoabsorption cross sections in calcium isotopes. Large-scale shell-model calculations with the Lanczos method are adopted. The photoabsorption cross sections in calcium-48 are excellently reproduced. The existence of a pygmy dipole resonance in calcium-52 is predicted.